Development of a reverse transcription-polymerase chain reaction assay for diagnosis of lymphocytic choriomeningitis virus infection and its use in a prospective surveillance study - Park, Jong Y.; Peters, C. J.; Rollin, Pierre E.; Ksiazek, Tom G.; Gray, Barry; Waites, Ken B.; Stephensen, Charles B. (Journal of medical virology, 1997)
Lymphocytic choriomeningitis virus (LCMV), which is one of several arenaviruses that are pathogenic for humans, causes encephalitis and meningitis in man. In this study, single‐stage and nested reverse transcription‐polymerase chain reaction (RT‐PCR) assays were developed that targeted the GPC and N genes of LCMV. Both assays detected <1 TCID50 unit of LCMV. These assays were used to measure the incidence of LCMV infection by testing cerebrospinal fluid (CSF) samples with ⩾10 leukocytes/μI collected over 1 year from patients undergoing lumbar puncture for diagnostic reasons at two Birmingham hospitals. Samples were tested for the presence of LCMV RNA by using the RT‐PCR assay and for LCMV‐specific IgM antibody by using an ELISA assay. None of the specimens collected from 813 patients was positive by either assay. Although no cases of acute infection were detected, 4% (11/272) of serum collected from a subset of patients was positive for LCMV‐specific IgG. A significantly greater rate of seropositivity was found among subjects over 60 years of age (9.4%; P < 0.025) than was found in younger subjects (2.4% at 30–59 years of age; 0% at <30 years of age). These data suggest that serious central nervous system disease due to LCMV infection is not common in this population. The high rate of seropositivity in those over 60 years of age suggest that infection was once more common. J Med Virol 51:107–114, 1997. © 1997 Wiley‐Liss, Inc.